Geochemistry of potentially hazardous elements in loess-amended mining sediment. (August 2020) - Zang, Fei; Wang, Shengli; Nan, Zhongren; Zhao, Chuanyan
Abstract: Contaminated mining sediment may cause environmental and human health risk due to potentially hazardous elements (PHEs) leaching into groundwater, especially under very acid (pH ≤ 3) conditions. The capability of Chinese loess to immobilise and retain copper (Cu), zinc (Zn), cadmium (Cd) and lead (Pb) from element contaminated mining sediment was explored by a column leaching experiment. Results showed that loess could effectively reduce Cu geomobility, and their leachate concentrations were lower than the quality standard (1.0 mg L −1 ) for ground water in China. The sierozem showed strong adsorption for Zn, Cd and Pb. The geomobility of Cu, Zn, Cd and Pb were affected by pH, electrical conductivity, organic matter and carbonate content of sediment/loess-amended sediment and sierozem. The long-term leaching of PHEs in loess-amended sediment may pose a potential risk to sierozem and groundwater in the region. This study highlights the need to develop a remediation technique to minimise the concentration level of hazardous elements in the mining sediment. Graphical abstract: Image 1 Highlights: Geochemistry of PHEs in loess-amended mining sediment was evaluated. Sierozem showed strong adsorption for Zn, Cd and Pb but weak adsorption for Cu. HNO3 leaching decreased the pH, EC, OM and CaCO3 content of different soil depths.